ECONOMIC FEASIBILITY OF NEW CHEMOTHERAPY REGIMENS FOR TREATMENT OF TUBERCULOSIS PATIENTS WITH EXTENSIVE DRUG RESISTANCE - I. A. Vasilyeva; A. G. Samoylova; A. V. Rudakova; O. V. Lovacheva; K. A. Glebov; L. N. Chernousova (Туберкулез и болезни лёгких)
The article presents economic feasibility evaluation for using high-priced drugs in the regimens for treatment of tuberculosis patients with extensive drug resistance.Subjects and Methods. Treatment efficiency was evaluated in 175 tuberculosis patients with extensive drug resistance, treated by four different regimens, including third line drugs and without them; the economic impact of each regimen was evaluated. Two types of pharmaco-economic analysis were used: costs – effectiveness and budget impact analysis.Results of the study. Despite the significant costs of regimens containing moxifloxacin, linezolid, and bedaquiline, the co-efficient of costs – effectiveness turned out to be the lowest. When using models for comparing costs and losses over 5 year period of XDR TB patients treatment it was found out that regimens containing moxifloxacin, linezolid and bedaquiline possessed significant economic predominance which required major investment at the initial stages of introduction, and by the end providing savings from 46.3 to 65.3% of the budget compared to the regimens without these drugs. The obtained results provide the evidence that use of regimens containing new highly effective drugs (moxifloxacin, linezolid and bedaquiline) in rational combinations with basic and reserve drugs, prescribed with consideration of drug resistance profile allow achieving the significant economic effect.